Sensory processing patterns in children with attention-deficit hyperactivity disorder: A case–control study - Bandyopadhyay, Aritra; Nath, Saswati; Mandal, Uday Sankar; Ghoshal, Sreeprova; Dandapath , Abhishek; Mallick, Suchismita (Asian Journal of Medical Sciences, 2024)
Background: Sensory processing (SP) indicates the ability of the nervous system to receive, analyze, process, and respond to external sensory input and coordinates motor movements accordingly. Children with various neurodevelopmental disorders, like autism spectrum disorder, have SP issues. However, studies regarding SP issues in attention-deficit/hyperactivity disorder (ADHD) compared to typically developing children are relatively less. Aims and Objectives: To study the SP pattern of children with ADHD, to compare with the control group, and to study the correlation of symptom severity with SP deficit in children with ADHD. Materials and Methods: All children attending the child guidance clinic at R. G. Kar Medical College and Hospital were screened, and children with ADHD without any other comorbid disorder as diagnosed by Diagnostic and Statistical Manual 5 were selected. Their ADHD symptom severity was assessed using the ADHD test, and SP was assessed using the Short Sensory Profile (SSP). Results: The SSP mean score of the children with ADHD was significantly different than the mean score of the control group, and the percentage of children having a definite difference in SP was significantly different in the ADHD children group compared to the control group. The severity of the SP deficit also correlates with the severity of ADHD symptoms, as found by the correlation study. Conclusion: Children with ADHD have shown a definite difference in SP compared to controls, and the severity of the sensory problem is proportionate to the severity of the symptoms of ADHD.